The relationships between quality management systems, safety culture and leadership and patient outcomes in Australian Emergency Departments. (5th February 2020) - Clay-Williams, Robyn; Taylor, Natalie; Ting, Hsuen P; Winata, Teresa; Arnolda, Gaston; Austin, Elizabeth; Braithwaite, Jeffrey
Abstract: Objective: We aimed to examine whether Emergency Department (ED) quality strategies, safety culture and leadership were associated with patient-level outcomes, after controlling for other organization-level factors, in 32 large Australian hospitals. Design: Quantitative observational study, using linear and multi-level modelling to identify relationships between quality management systems at organization level; quality strategies at ED level for acute myocardial infarction (AMI), hip fracture and stroke; clinician safety culture and leadership and patient-level outcomes of waiting time and length of stay. Setting: Thirty-two large Australian public hospitals. Participants: Audit of quality management processes at organization and ED levels, senior quality manager at each of the 32 participating hospitals, 394 ED clinicians (doctors, nurses and allied health professionals). Main Outcome Measure(s): Within the multi-level model, associations were assessed between organization-level quality measures and ED quality strategies; organization-level quality measures and ED quality strategies and ward-level clinician measures of teamwork climate (TC), safety climate (SC) and leadership for AMI, hip fracture and stroke treatment conditions; and organization-level quality measures and ED quality strategies and ward-level clinician measures of TC, SC and leadership, and ED waiting time and length of stay (performance). Results: We found seven statistically significant associations between organization-level quality systems and ED-level quality strategies; four statistically significant associations between quality systems and strategies and ED safety culture and leadership; and nine statistically significant associations between quality systems and strategies and ED safety culture and leadership, and ED waiting time and length of stay. Conclusions: Organization-level quality structures influence ED-level quality strategies, clinician safety culture and leadership and, ultimately, waiting time and length of stay for patients. By focusing only on time-based measures of ED performance we risk punishing EDs that perform well on patient safety measures. We need to better understand the trade-offs between implementing safety culture and quality strategies and improving patient flow in the ED, and to place more emphasis on other ED performance measures in addition to time.